Time‐variable gravity signal in Greenland revealed by high‐low satellite‐to‐satellite tracking. Issue 7 (30th July 2013) - Weigelt, M.; van, T.; Jäggi, A.; Prange, L.; Tourian, M. J.; Keller, W.; Sneeuw, N.
<x xml:space="preserve">Abstract</x> [1] In the event of a termination of the Gravity Recovery and Climate Experiment (GRACE) mission before the launch of GRACE Follow‐On (due for launch in 2017), high‐low satellite‐to‐satellite tracking (hl‐SST) will be the only dedicated observing system with global coverage available to measure the time‐variable gravity field (TVG) on a monthly or even shorter time scale. Until recently, hl‐SST TVG observations were of poor quality and hardly improved the performance of Satellite Laser Ranging observations. To date, they have been of only very limited usefulness to geophysical or environmental investigations. In this paper, we apply a thorough reprocessing strategy and a dedicated Kalman filter to Challenging Minisatellite Payload (CHAMP) data to demonstrate that it is possible to derive the very long‐wavelength TVG features down to spatial scales of approximately 2000 km at the annual frequency and for multi‐year trends. The results are validated against GRACE data and surface height changes from long‐term GPS ground stations in Greenland. We find that the quality of the CHAMP solutions is sufficient to derive long‐term trends and annual amplitudes of mass change over Greenland. We conclude that hl‐SST is a viable source of information for TVG and can serve to some extent to bridge a possible gap between the end‐of‐life of GRACE and the availability of GRACE Follow‐On.